Prevalence and clinical impact of frailty in COPD: a systematic review and meta-analysis - Wang, Lina; Zhang, Xiaolin; Liu, Xinmin (BMC pulmonary medicine, 2023)
Frailty has been increasingly identified as a risk factor of adverse outcomes in chronic obstructive pulmonary disease (COPD). The prevalence and impact of frailty on health outcomes in people with COPD require clarification. PubMed, Embase, The Cochrane Library and Web of Science (January 1, 2002, to July 1, 2022) were comprehensively searched to identify studies related to frailty and COPD. Comparisons were made between people who did and did not have frailty for pulmonary function, dyspnea severity, 6-minute walking distance, activities of daily life, and mortality. Twenty studies (9 cross-sectional, 10 cohort studies,1 clinical trial) from Europe (9), Asia (6), and North and South America (4), Oceania (1) involving 11, 620 participants were included. The prevalence of frailty was 32.07% (95% confidence interval (CI) 26.64-37.49) with a range of 6.43-71.70% based on the frailty tool used. People with frailty had lower predicted forced expiratory volume in the first second (mean difference - 5.06%; 95%CI -6.70 to -3.42%), shorter 6-minute walking distance (mean difference - 90.23 m; 95%CI -124.70 to -55.76), poorer activities of daily life (standardized mean difference - 0.99; 95%CI -1.35 to -0.62), higher CAT(COPD Assessment Test) score(mean difference 6.2; 95%CI 4.43 to 7.96) and mMRC (modified Medical Research Council) grade (mean difference 0.93; 95%CI 0.85 to 1.02) compared with those who did not (P < 0.001 for all). Meta-analysis showed that frailty was associated with an increased risk of long-term all-cause mortality (HR 1.68; 95% CI 1.37-2.05; I = 0%, P < 0.001). Frailty is prevalent in people with COPD and linked with negative clinical outcomes including pulmonary function, dyspnea severity, exercise capacity, quality of life and mortality.